[Woman on runway wearing dark patterned dress, Black Heritage]
The Black woman is also wearing hoop earrings, and no shoes. There is a plant located next to the runway on the lower left foreground of the image. To the lower right foreground of the image, there is a man wearing a a dark colored shirt seated at a dinner table. Behind the runway, there is also a group of people seated at a dinner table looking at the woman walking down the runway. The tables have coffee mugs and a coffee plot placed on them. Photo taken during BSU's 'Black Odyssey '72' Heritage Week Fashion Show.